Impact of different silkworm dietary supplements on its silk performance - Nicodemo, Daniel [UNESP]; Oliveira, Juliano E.; Sedano, Anderson Aparecido [UNESP]; Marconcini, Jose Manoel; Tonoli, Gustavo H. D. (Springer, 2014)
This study aims to evaluate the effect of silkworm larva (Bombyx mori) diet supplementation with two amino acids (threonine and valine) on the cocoon production and on the structural and mechanical properties of the silk produced. Negligible morphological differences were observed in the silk fiber threads from silkworm larvae supplemented with the tested amino acids. Higher production (yield) of silk was obtained using threonine in the diet of the silkworm. The treatments with threonine have increased the limit of proportionality, tensile strength, toughness, and maximum deformation of the thread of silk fibers. No significant increment in these properties was observed due to the increase in the threonine content. The treatments with valine led to lower increase in tensile strength and toughness. The real density of the silk has decreased with the use of supplements. The present study contributes to engineering of advanced silk materials, which should be attractive candidates for multipurpose applications.